The mechanism underlying ICAM-1 and E-selectin-mediated hypertriglyceridemic pancreatitis-associated lung injury. (December 2022) - Yu, Rong; Hou, Chaoqun; Peng, Yunpeng; Zhu, Xiaole; Shi, Chenyuan; Huang, Dongya; Miao, Yi; Li, Qiang
Abstract: Purpose: To investigate the possible mechanism by which adhesion molecules ICAM-1 and E-selectin mediate hypertriglyceridemic pancreatitis (HTGP)-associated lung injury. Methods: C57BL/6 mice were randomly divided into five groups: control group (Con), severe acute pancreatitis group (SAP), HTGP group (HTGP), A-205804 group (A-205804), and apocynin group (Apo). Serum biochemical markers related to pancreatitis, such as inflammatory cytokines, amylase and lipase, were measured by enzyme-linked immunosorbent assay (ELISA) kits. Hematoxylin and eosin (HE) staining was used to analyze the histopathology changes in the pancreas and lung, and myeloperoxidase (MPO) activity in lung was detected by immunohistochemistry (IHC). Molecules related to NF-κB signaling pathway and adhesion molecules were assessed by western blotting (WB), IHC and immunofluorescence staining. The levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH) in lung tissues and serum were measured with reagent kits, respectively. Results: The severity of pancreatitis and lung injury in HTGP group was more severe than that in SAP group, and the expression levels of adhesion molecules ICAM-1 and E-selectin in lung tissues of HTGP mice were significantly increased. After HTGP mice were treated with adhesion molecule inhibitor A-205804, the expression of ICAM-1 and E-selectin in A-205804 group significantly decreased, and the lung injury was alleviated. The HTGP group had higher levels of oxidative stress and NF-κB pathway-related protein p-p65 expression compared with the SAP group. Apocynin treatment resulted in suppression of p-p65, ICAM-1, and E-selectin expression. Conclusion: In HTGP, hypertriglyceridemia may exacerbate pancreatitis-related lung injury by regulating oxidative stress and activating the NF-κB proinflammatory pathway to upregulate ICAM-1 and E-selectin levels. Highlights: The potential mechanism of lung injury in hypertriglyceridemia acute pancreatitis is proposed. The mechanism depends on the effect of oxidative stress on some adhesion molecules. Adhesion molecules ICAM-1 and E-selectin may be the targets for treatment of hypertriglyceridemia acute related lung injury.